Ética em educação: novos paradigmas para nosso tempo - Führ, Regina Candida (2011)
Ethics in education: new paradigms for our time is the subject of this study. It started of the anxieties of research with schools of the Congregation of St. Catherine Association. The results of these studies were socialized with teachers, through workshops in schools of the Association, for debate and reflection of questions concerning subject matter in study. The reflection, the share and historic look launched to the charism of Regina Protmann and the origin of the congregation, offered important elements, pointing out the ethics in education in a great challenge, and an ethical commitment as a requirement of fidelity to the charism of the founder of the congregation. The act of educating is an ethic act, then its impossible escape of ethic decisions, from choice of contents until the method that must be used or the form of relationship with the students and educators. New paradigms in education are important for people dive in a culture of sense of life. This experience shared with educators was important to the investigation that is being showed. The research had an qualitative approach and participant. The narratives of the participants were collected through supplementaries interviews of the seminars. These data were summarized and mapped, using the principle of analyzing the content. Studies of Freire, Dussel, Susin, Boff, Gibellini, Andreola, Bauman, Küng, Lévinas, Bonhoeffer, Morin, Boaventura de Souza Santos, Taille and André gave the main support to the comprehension of the reflections socialized by educators, students and parents. Together with several authors and in confrontation with the practice and charism of the founder, passed an interactive dialogue where it was possible the construction of a new author. The results confirmed that ethic in education with new paradigms, requires a new set of educationals practices and socials that gave importance and commitment with the human care- ecological.